Financial regulation and supervision in emerging markets: The experience of Latin America since the Tequila Crisis - Barbara Stallings; Rogerio Studart (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
The paper deals with changes in the regulation and supervision of the Latin American financial sector in the aftermath of the `Tequila Crisis' of 1994–95. While it finds that both have improved, regulation and supervision cannot resolve all problems; good macroeconomic policy and performance are essential complements. This is especially true because of the procyclical nature of financial activity. The paper presents both regional data for Latin America, contrasting it with other emerging markets, and four country case studies (Argentina, Brazil, Chile, and Mexico). The latter show how individual country characteristics and experiences affect the operation of the financial systems. We close with some policy recommendations. – regulation ; banking ; Latin America
Keywords: N26; N46; O54; 330; Bank; Regulierung; Bankenaufsicht; Lateinamerika